A Comparison of Derivational and Inflectional Morphemes between Nusa Penida Dialect and Sepang Dialect - ., Ni Putu Sri Merta Utami; ., Dr. I Gede Budasi,M.Ed,Dip.App.Lin; ., Dewa Putu Ramendra, S.Pd, M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
This study aimed at describing the comparison of prefixes and suffixes in Nusa Penida Dialect and Sepang dialect which belong to derivation and inflection. This research was a descriptive qualitative research. Two informants sample of Nusa Penida were chosen based on a set of criteria. The data were collected based on three techniques, namely: observation, recording technique, and interview (listening and noting) technique. The results of the study showed that those ware difference: prefix {mÉ™-}: NPD: tÎ›lÊŠh (V) become mÎ›tÎ›lÊŠh (V) and when prefix {mÉ™-} + kÎ›ndÎ› (N) become mÎ›kÎ›ndÉ™ (V). suffix {-In}: NPD klÎ›mbI (N) become klÎ›mbIn (V). suffix {-Ä“ }: SP: tÎ›bIng (V) become tÎ›bIngÎ› (V) and NPD: JÇlÇmÇ (N) become JÇlÇmÎ›tÄ“ (N). The similarity prefix {mÉ™-}: NPD and SP: {mÉ™-} + jÎ›lÎ›n (N) become mÉ™jÎ›lÎ›n (V),. Prefix {m-} NP and SP: {m-} + bÊŠbÊŠh (N) become mÊŠbÊŠh (V). suffix {-Î›Å‹} NP and SP: sÎ›mpÎ›t (N) + {-Î›Å‹}â†’ become sÎ›mpÎ›tÎ›Å‹ (V). Suffix {-In} NP and SP: nÉ’t (V) + {-In} â†’ become nÉ’tIn (V). keyword : Derivational Morpheme, Inflectional Morpheme, Nusa Penida Dialect and Sepang dialect.